The Pursuit of Health through Faith Healing: An Anthropological Analysis of Personalistic Belief System - Ayub, Bisma; Syed, Aiman Ali; Zulfiqar, Humaira (Annals of Human and Social Sciences, 2024)
This study describes the phenomenon of faith healing by investigating various factors that motivate people to seek treatment and cure through faith. This ethnographic study has been conducted at HMC Housing Colony Taxila. The researcher has used purposive sampling technique to conduct this research. In-depth interviews have been taken with the colony residents as well as visitors at the shrine Baba Musafir Shah at HMC Colony Taxila. The findings of this research reveal that religious rituals bind individuals together.Media, including print or electronic and religious scholars play a vital role in making people attentive of the fact that faith healing helps an individual for healing. All aspects of one’s life go through significant changes as a result of modernization, globalization, and social change. This research will contribute to the existing knowledge by providing evidence based faith healing practices, and hence will provide bases for the future researchers to integrate faith healing into mainstream healthcare, promoting a holistic approach to wellness.